(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Inflammation and discomfort in the joints are symptoms of arthritis, a crippling disease that impacts millions of people throughout the globe. The quest for alternative remedies is driven by the fact that conventional medications often have negative effects. Cymbidium species are orchids that have a long history of usage in ethnomedicine, and this research seeks to learn more about their anti-arthritic properties. The major objective of this study is to investigate the possibility of extracts from Cymbidium species as natural treatments for arthritis by assessing their anti-arthritic efficacy in in vitro and in vivo investigations. Researchers used solvents of different polarity to extract bioactive chemicals from different parts of several Cymbidium species’ plants, including their leaves, stems, and roots. A preliminary phytochemical screening was performed on the extracts to detect the presence of anti-inflammatory chemicals such as tannins, saponins, flavonoids, and others. The anti-arthritic efficacy was evaluated in vitro via the use of protein denaturation and membrane stabilization tests. Using Freund’s complete adjuvant, an arthritis model was established in Wistar rats for the in vivo experiments. Arthritis symptoms were assessed by assessing paw edema, joint diameter, and histological alterations in response to Cymbidium extracts. The extracts from Cymbidium included many bioactive chemicals, as shown by phytochemical investigation. Protein denaturation and red blood cell membrane stability were both markedly inhibited in in vitro tests, suggesting strong anti-inflammatory action. Treatment significantly reduced paw edema and joint swelling in rats as compared to the control group, according to in vivo investigations. The anti-joint properties of Cymbidium extracts were further validated by histopathological analysis. Based on the results of this research, it seems that some species of Cymbidium have bioactive chemicals that work together to alleviate arthritis. Based on these findings, Cymbidium extracts may be useful as an alternative to conventional arthritic treatments. Completely determining their safety and effectiveness in people requires more study including clinical trials.